Penyuluhan Pencegahan Stunting dengan Diskusi Interaktif di Desa Dukuhmencek - Aryani Ayuning Tyas; Berliana Albanita; Yanu Ardiani; Anggritiyan Ariyanto; Anis Rofi Hidayah; Abdul Hadi; Werdining Wulan; Nurul Lailatul Vitriah; Ari Septianingtyas Purwandhini; Moh. Qurtubi (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Stunting is a chronic nutritional problem that arises as a result of malnutrition that lasts long enough. Factors that can affect the incidence of stunting are directly influenced by infectious diseases and lack of nutritional intake in quality and quantity. The indirect factors are socioeconomic factors, parental education, parental employment, exclusive breastfeeding, immunization status, reach of health care facilities and inadequate parenting. The problem of stunting is a concern considering the numbers are still high in Indonesia. This includes Jember Regency. According to the Indonesian Ministry of Health in the results of the Indonesian Nutrition Status Survey in 2022 (in radarjember.jawapos.com) has placed Jember as the area with the highest prevalence of stunted toddlers in East Java with a percentage reaching 34.9 percent. The method used was counseling by socializing and asking questions about stunting to cadre mothers and local mothers in Dukuhmencek Village, one of the villages in Jember. Activities were carried out in each hamlet in this village which includes Krajan Hamlet, Ampo Hamlet, and Botosari Hamlet. In the implementation, we provided posters containing stunting prevention as an effort to continue to improve health status in order to reduce stunting rates in the surrounding area